Potential value of bacteriocins in the etiological treatment of infectious diseases of the respiratory tract - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2017)
Bacteriocins are ribosomal-synthesized hydrophobic antimicrobial peptides with a broad antimicrobial spectrum of action. Gram-positive bacteria are the main source of bacteriocins. Bacteriocins of different classes acting on Gram-positive and Gram-negative bacteria use different molecular mechanisms, the functioning of which leads to disruption of the integrity of the cell wall or inhibition of the synthesis of nucleic acids and proteins of targeted bacteria. Currently, more than 100 lantibiotic peptides are described in the literature. Many of them are used to develop future medicines. Several lantibiotics are currently undergoing clinical and preclinical trials, including bioengineering lantibiotics, which can play a key role in overcoming the antibiotic resistance of bacterial pathogens.